(untitled) - Tsuda, Noritake (Tokyo, 1937)
In Japanese art there are many things which inevitably appear strange to Western eyes. For example, subjects of Buddhist painting are almost unthinkable to Westerners. The greatness of Japanese-ink landscape painting is exceedingly difficult to understand because of the deep meaning which is hidden from those who have not been initiated into the mystery of Japanese landscape painting in black and white.
Keywords: Art, japanese; History